COMPARISON OF DOPPLER ULTRASONOGRAPHY AND TRANSPULMONARY THERMODILUTION WHEN ANALYZING HEMODYNAMICS IN THE CHILDREN WITH SEVERE THERMAL INJURY - A. U. Lekmanov; D. K. Azovskiy; S. F. Pilyutik (Вестник анестезиологии и реаниматологии)
Goal of the study: to compare rates of central hemodynamics, obtained through Doppler ultrasonography and transpulmonary thermodilution in the children with massive burns. Material. 15 children were included into observatory prospective study: 9 (60%) boys and 6 (40%) girls in the age from 1 to 17 years old (9.27 ± 4.85) with burns of the surface from 30 to 70% (53.00 ± 11.14). Children were treated in the intensive care department of Speransky Children Municipal Clinical Hospital no.9 from 01.07.2013 to 01.07.2016. Methods. Transpulmonary thermodilution technique of PiCCO (Pulse index Contour Continuous Cardiac Output, Pulsion Medical Systems, Germany) was used to assess parameters of central hemodynamics. Doppler ultrasonography (USCOM, Sydney, NSW, Australia) was used for non-invasive assessment. The following rates were compared: CI (cardiac index) in L ∙ min-1 ∙ m-2 stroke volume index (SVI) in ml/m2 , total peripheral vascular resistance (TPVR) in dyn ∙ s ∙ cm-5/m2 . The initial data were collected in 60 minutes after the child's admission to hospital. Further they were registered each 6 hours during 48 hours. Results. 120 invasive assessments of central hemodynamics were done as well as 120 non-invasive ones. While comparing techniques of Doppler ultrasonography and transpulmonary thermodilution, the relative difference between two methods evaluated by three rates varied from -4 to 5%. Statistically significant difference was found out only for CI within the period from 18 to 30 hours: p = 0.04089 and p = 0.01857. Bland–Altman plot was used for analysis of several follow-up periods of the same patient; methods demonstrated the satisfactory agreement of the assessment results. Conclusions. The hypothesis about the comparability of data obtained through invasive and non-invasive techniques for central hemodynamics testing in the children with massive thermal injury has been confirmed.